L’odio proibito: la repressione giuridica dello hate speech (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Discorsi odiosi - 2. La repressione giuridica delle idee odiose: vecchie difese, nuovi difesi - 3. Le ragioni del contrasto giuridico ai discorsi d’odio - 4. Due direttrici nella giustificazione della repressione giuridica del discorso d’odio.Forbidden hate: the legal repression of hate speechABSTRACT: The aim of this article is two-folded. First, it offers a general overview of the legal repression of various categories of expressive behaviours ascribed to the notion of hate speech. Especially in Europe, such repression often passes through criminalization, long since used by law to suppress thoughts or points of view for some reason considered harmful. The social groups nowadays protected by such repressive measures, however, are different from the past: weak and/or minoritarian groups rather than strong and/or majoritarian ones. The second aim of this work is to identify the reasons for the legal repression of expressions, beliefs or doctrines certainly in many cases morally deplorable, yet protected by other high-ranking legal reasons: the principles of freedom of thought and speech. It will be noted that especially for untargeted hate speech not connected to a clear and present danger of unlawful actions, there is no general agreement about those reasons. Furthermore, they tend to be structured in justifications showing some typical flaws of, respectively, deontological and teleological reasoning: the former tend to be superficial as apodictic, generic and vacuous; the latter tend to evade the argumentative burdens of factual order from which their validity depends.